A Comprehensive Framework for Human Resource Development: Implementing the ADDIE Model in Public Service Management - Sabrina Rahma Widhiyanti; Riyuzen Praja Tuala; Devin Cumbuan Putri (Journal of Educational Management Research, 2026)
Management training and development source Power human (HR) has role important in increase performance employee at an organization. This research aims to analyze human resource training and development management based on the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) in increasing employee performance. Research This use approach qualitative with technique data collection through interviews, observations, and documentation. Research results show that implementation of the ADDIE model has implemented in a way systematic through stages analysis needs, program design, development material, implementation training, as well as evaluation. The training program implemented has in accordance with need employees, but improvement performance Not yet completely optimal because influenced by factors implementation, limitations mean infrastructure, as well as burden Work employees. Although thus, training still give contribution to improvement competence, efficiency work and quality service. With Thus, the ADDIE model can become effective framework in management human resource training and development, although still required strengthening at the stage implementation and evaluation for reach more optimal and sustainable results.